Enhancing Humanitarian Efforts Through Diplomatic Networks : A Study Case of International Committee of The Red Cross Humanitarian Diplomacy in Creating Funding Mechanism - Mubin, Sayyidul (Jurnal Pena Wimaya, 2023)
Humanitarian diplomacy is an effort to protect human beings, especially in conflict areas. The ICRC's worldwide humanitarian operations require sufficient funding to carry out its activities. Development of the direction of ICRC's humanitarian diplomacy is also being carried out to provide maximum impact on humanitarian issues. This paper will answer how the ICRC builds a funding network through humanitarian diplomacy. This study uses Literature Reviews from books and journals regarding humanitarian diplomacy as a basis for thinking in writing. A qualitative pattern is used to process the findings and data obtained from the results of a literature review of articles, books and journals related to the research topic. This research uses descriptive analysis so that the author will examine the data obtained in the form of news, reports, statements and books. which discusses the activities of the ICRC. The result of this research is that the ICRC builds community networks with state and non-state actors to ensure funding for the organization's operations. This effort is carried out by the ICRC to ensure that their humanitarian operations continue, so that there is no reason why funds are a problem in the organization's humanitarian operations.